Editorial Board - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
After hard and tedious efforts for several months, finally the second edition of JIFAM can be published as JIFAM, Volume 1, Issue 2, September 2019. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for the second issue.